Soldagem por fricção e mistura da liga de alumínio AA2198-T851 em chapas de diferentes espessuras - Moroz, Ivan (2012)
Friction Stir Welding (FSW) process, conceived in 1991, has been the target of research in the last decades due to the excellent properties presented by its welded joints, favored by the fact of occurrence in the solid state, and easiness of application, enabling several weld geometries. In particular, metal alloys with low melting points, in which conventional methods of welding (based in fusion) are hard to apply, have been benefited by this method, with large application in automobilist and aerospace industrial sectors. These branches enterprises are interested in determining the set of parameters that will yield the best mechanical properties, before utilizing FSW in commercial scale. With this objective in mind, this work aimed at optimizing the FSW parameters in the Aluminum Alloy 2198-T851, considering geometry of plates of different thicknesses (tailor welded blanks configuration). Due to the asymmetric characteristic of the welded joints, welding parameters related to positioning of the welding tool (welding angles and pin offset) were varied, in two groups of plates of different thicknesses: 4.2-3.5 milimeters, and 4.2-2.5 milimeters. Results obtained from macro and microstructural characterization (optical microscopy), tension tests and microhardness analyses were considered as criteria for determining the best quality welds. After the analysis of these results and correlation with related literature, it was concluded that the proposed variation in welding parameters affects the flux of material in the welded joint, possibly leading to formation of defects, causing a detrimental effect on the mechanical properties. Nevertheless, welds with mechanical properties equal to or superior to the base metal were obtained (except for elongation values), especially in relation to yield stress values, of capital importance in industrial sectors associated with high security demands, such as automobilist and aerospace.